Postcolonial Theory and Cultural Resistance: Recovering Voice and Mind (The International Journal of Educational Sciences and Arts, 2024)
The importance of this study lies in its attempt to monitor the efforts of cultural resistance in the context of postcolonial theory. It aims to address two problems that lie at the heart of this resistance: the restoration of the suppressed voice, and the occupied mind of the colonized. The study is guided in addressing these two problems by the cultural approach, which provides the researcher with mechanisms and procedures that enable him to extrapolate the cultural phenomenon and its representations in its various manifestations, so he works on analyzing, describing and interpreting it. The study showed that the former colonists, when they possessed the language and various tools of expression, provided new creative and critical experiences, and a cultural discourse that differs from the speech of the colonizers, and works to undermine the foundations on which it was based.
Keywords: Cultural Resistance; Postcolonialism; Suppressed Voice; Conquered Mind